2008
DOI: 10.1016/j.cgh.2007.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Incident Gallbladder Disease in Pregnancy

Abstract: Background and Aims-Insulin resistance is associated with prevalent gallstones, but its effect on initial gallstone formation is not well understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…Resolution frequently transpires during the post-partum period: sludge disappears in two-thirds; small (<1 cm) gallstones (microlithiasis) vanish in one-third, but definitive gallstones become established in ~5% 75,76. Additional risk factors for stone formation during pregnancy include obesity (prior to the pregnancy), reduced high density lipoprotein (HDL) cholesterol and the metabolic syndrome 76,77…”
Section: Gallstone Diseasementioning
confidence: 99%
“…Resolution frequently transpires during the post-partum period: sludge disappears in two-thirds; small (<1 cm) gallstones (microlithiasis) vanish in one-third, but definitive gallstones become established in ~5% 75,76. Additional risk factors for stone formation during pregnancy include obesity (prior to the pregnancy), reduced high density lipoprotein (HDL) cholesterol and the metabolic syndrome 76,77…”
Section: Gallstone Diseasementioning
confidence: 99%
“…Ko and colleagues [75] compared 205 women with new gallbladder sludge or stones during pregnancy against 443 controls. Logistic analysis showed that the effect of BMI was attenuated after adjusting for insulin resistance.…”
Section: Case-control Studies Of Habitual Physical Activity and Gallbmentioning
confidence: 99%
“…Importantly, oral contraceptives also affect the risk of gallstone formation, pointing at the role of endocrine factors [44], likely mediated by progesterone effects on gallbladder contractility [45]. Additional endocrine changes have since been identified, which also affect the chemical composition of bile and thus promote stone formation [46,47].…”
Section: Etiologymentioning
confidence: 99%